The long non-coding RNA-encoded microprotein MKKS3 drives colorectal cancer chemoresistance - Hui-Fang Hu; Qi Zhou; Jia-Zhen Huang; Jia-Ying Fu; Zhi-Ting Zuo; Qing-Yu He (Experimental & Molecular Medicine, 2026)
Abstract Although oxaliplatin is widely used in the frontline treatment of colorectal cancer (CRC), CRC recurrence is commonly observed owing to oxaliplatin resistance. The roles of long non-coding RNAs-encoded microproteins in oxaliplatin chemoresistance remain inadequately explored. In this study, a CRISPR/Cas9 library was developed to target previously identified 314 microproteins translated from long non-coding RNAs, followed by functional screening. This strategy identified MKKS3, encoded by NR_072977, as a key regulator of chemoresistance in CRC. A pan-cancer analysis integrating translatomics and proteomics revealed widespread MKKS3 expression across various human cancers. Our experiments demonstrated that MKKS3 promotes chemoresistance in CRC and drives iCAF-to-myCAF conversion. Mechanistically, MKKS3 interacts with TRIM29 to facilitate DNA repair complex assembly and induce STING ubiquitination, thus suppressing IFNβ secretion and further activating fibroblasts. These activated fibroblasts secrete increased amounts of TGFβ, which in turn downregulates STING expression. Additionally, DENR functions as a suppressor of MKKS3 expression and regulates its translation. The natural compound 1-Hydroxybaccatin I inhibits the MKKS3–TRIM29 interaction, and its combination treatment with oxaliplatin enhances therapeutic outcomes of CRC by promoting CD8 + T cell activation and tumour infiltration. Moreover, intratumoural injection of AAV8-shMKKS3 with oxaliplatin produces a synergistic anti-tumour effect. Collectively, MKKS3 drives CRC chemoresistance through the TRIM29–STING–IFNβ–TGFβ axis. This study provides novel insights into the mechanism of MKKS3 in regulating chemoresistance and providing a potential therapeutic target for reversing the chemoresistance of CRC.